127 Circumstances associated with suicides among American Indian/Alaska Native Persons — NVDRS, 2015–2020. (20th November 2022) - Ivey-Stephenson, Asha; Trinh, Eva; Zhou, Hong; Welder, Laura; ,; Stone, Deborah; Fowler, Katherine
Abstract : Background: Suicide disproportionately affects American Indians/Alaska Native persons (AI/AN), and in 2020 non-Hispanic AI/AN persons had the highest rate of suicide (27.7 per 100, 000); nearly double their rate in 2000. Aim: These data will examine associated characteristics and circumstances of suicide between AI/AN and non-AI/AN populations to inform prevention. Methods: National Violent Death Reporting System (2015–2020) data will be used to compare suicide characteristics and circumstances associated with suicide between AI/AN and non-AI/AN persons. Data through 2019 include 42 states, D.C., and Puerto Rico (2020 to be added prior to presentation). Data were abstracted from death certificates, and law enforcement/medical examiner/coroner reports. Results: Preliminary results indicate available circumstance information was known for 85.9% of AI/AN persons versus 90.4% of non-AI/AN persons. Intimate partner problems were a common precipitating circumstance for both AI/AN (37.3%) and non-AI/AN persons (26.9%), but with significantly greater odds among AI/AN persons (aOR = 1.4; 95% CI = 1.3–1.6). Additionally, AI/AN persons had 1.6 (95% CI = 1.3–2.0) times greater odds of the suicide of a friend or family member affecting their death, compared to non-AI/AN persons. Additional results highlighting similarities/differences in circumstances and other characteristics (e.g., method, veteran status) will be presented. Outcomes: The high rate of suicide and higher odds of experiencing various suicide circumstances among AI/AN persons (compared to non-AI/AN persons) highlight some of the inequities faced by this population. This study highlights the importance of a comprehensive approach to suicide prevention that incorporates culturally inclusive strategies based on the best available evidence.